Focus on the tumor microenvironment: A seedbed for neuroendocrine prostate cancer - Zhou, Hengfeng; He, Qiangrong; Li, Chao; Alsharafi, Bassam Lutf Mohammed; Deng, Liang; Long, Zhi; Gan, Yu (Frontiers in Cell and Developmental Biology, 2022)
The tumor microenvironment (TME) is a microecology consisting of tumor and mesenchymal cells and extracellular matrices. The TME plays important regulatory roles in tumor proliferation, invasion, metastasis, and differentiation. Neuroendocrine differentiation (NED) is a mechanism by which castration resistance develops in advanced prostate cancer (PCa). NED is induced after androgen deprivation therapy and neuroendocrine prostate cancer (NEPC) is established finally. NEPC has poor prognosis and short overall survival and is a major cause of death in patients with PCa. Both the cellular and non-cellular components of the TME regulate and induce NEPC formation through various pathways. Insights into the roles of the TME in NEPC evolution, growth, and progression have increased over the past few years. These novel insights will help refine the NEPC formation model and lay the foundation for the discovery of new NEPC therapies targeting the TME.